Traces of Biophilic Design in Anatolian Seljuk Architecture: Natural Shapes and Forms (Architecture Image Studies, 2025)
According to Aristotle, the primary source of all human actions and works is nature. When Albert Einstein said, "Look deeper into nature, then you will understand everything better," he said a key sentence in architecture, which is the field where the human-nature relationship turns into the most concrete products, as in every field of science. Every architectural structure is a historical indicator of the nature-human relationship. Biophilia is a concept used to describe the innate human tendency and need for a close connection with nature and other life forms. It is a concept that describes man's innate emotional attachment to other living organisms. Incorporating plants, water, and animals into the design of a space is one way to create a biophilic environment. The first fundamental dimension of biophilic design is an organic or natural dimension, defined as the shapes and forms in the built environment that directly, indirectly or symbolically reflect the human sensitivity inherent in nature. The second fundamental dimension of biophilic design is a place-based or local dimension, defined as buildings and landscapes that connect to the culture and ecology of a place or geographic region. The two basic dimensions of biophilic design relate to the six biophilic design elements: Environmental features, Natural shapes and forms, Natural patterns and processes, Light and space, and Space-based relationships. In this study, studies on structures such as mosques, madrasahs, healing houses, tombs, caravanserais, castles and palaces in Seljuk architecture were examined according to the dimension of biophilic design defined as natural shapes and forms in the built environment. Traces of biophilic design have been investigated in interior and exterior facade design, in minaret, mihrab, pulpit, console, arch, iwan, profiles, window arches, vaults and column capitals, as well as in the structural elements of crown doors, niches, windows, wall borders and crown arches. From the qualities of natural shapes and forms; Plant motifs, animal motifs, seashells and spirals, egg oval and cylindrical shapes, arches, vaults, domes, straight and non-right-angled forms were evaluated in terms of traces of biophilic design. It is thought that the research can contribute to today's understanding of biophilic design, and the applications made for this purpose, with the features of Seljuk buildings in terms of biophilic design.